Sosialisasi Literasi Digital di SMPN 1 Jiwan dalam Membangun Budaya Komunikasi Siswa Beretika di Ruang Digital - Nurin Ibnu Bachron; Vivian Agustina; Apvionita Ayu Salsabila; Nur Azis; Hendra Kurniawan; Maria M. Widiantari (Jurnal Pengabdian Masyarakat, 2026)
The rapid development of digital technology has significantly influenced students’ communication patterns, particularly in social media use, which is often not accompanied by adequate ethical awareness. Limited understanding of digital communication ethics may lead to negative behavior in online spaces. This activity aimed to enhance students’ digital literacy and foster ethical communication practices. The method employed was an educational socialization program conducted through material presentation, interactive discussions, and question-and-answer sessions involving eighth-grade students of SMPN 1 Jiwan. The results indicate an improvement in students’ understanding of social media ethics, awareness of digital footprints, and responsible information sharing. High levels of student enthusiasm and active participation during the activity reflect the effectiveness of the program. In conclusion, digital literacy socialization is effective in strengthening ethical digital communication awareness among junior high school students.